TANAMAN OBAT, TANAMAN UPACARA DAN PELESTARIAN LINGKUNGAN - Nyoman Adiputra (Environmental Research Center (PPLH) of Udayana University, 2011)
The existence of medicinal plant in Bali is a factual thing, as it is shown by the lontar usada Bali. On the other hand the ceremonial plants could not be forgotten. The question now, is there any relationship between these two plants? Does the relationship could be used in the environmental conservation program? It is hypothesized that some of the medicinal plants belong to the ceremonial plants; through horticulture the conservation of medicinal plants and ceremonial plants could be done. Therefore, walk-through surveys had been conducted in some hotels and governmental offices in Badung and Denpasar region. The results shown: that the horticulture planted belong to the medicinal plants, ranged from 46.5 %-78.2 %; and 50.0 % - 78.2 % belong to the ceremonial plants as well. It is concluded that through the horticulture, the conservation of living environmental could be done; therefore, the existence of medicinal and ceremonial plants could be maintained and become a reality until forever.